2010
DOI: 10.1136/adc.2009.170787
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of proportional assist ventilation

Abstract: During PAV, unloading does reduce inspiratory load, but there are wave form abnormalities and a time lag in delivery of the inflation pressure. The impact of these problems needs careful evaluation in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Although the infants currently studied were all ventilator dependent beyond 1 week after birth, their respiratory system resistances were not found, on average, to be very high; the median respiratory system resistance was 86.5 (range 85–174) cm H 2 O/L/s. We have previously demonstrated that the likelihood of oscillations appearing in the airway pressure waveform was greater when elastic unloading was used in a low compared with a high resistance model 5. In addition, in the in vitro model,5 oscillations in the airway pressure waveform appeared when the resistive unloading was greater than 100 cm H 2 O/L/s.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the infants currently studied were all ventilator dependent beyond 1 week after birth, their respiratory system resistances were not found, on average, to be very high; the median respiratory system resistance was 86.5 (range 85–174) cm H 2 O/L/s. We have previously demonstrated that the likelihood of oscillations appearing in the airway pressure waveform was greater when elastic unloading was used in a low compared with a high resistance model 5. In addition, in the in vitro model,5 oscillations in the airway pressure waveform appeared when the resistive unloading was greater than 100 cm H 2 O/L/s.…”
Section: Methodsmentioning
confidence: 96%
“…If after 10 min the infant remained stable and no airway pressure waveform abnormalities were observed, the unloading was increased to 100%. If airway pressure waveform abnormalities were then noted,5 the unloading was reduced back to 75%. Although the infants currently studied were all ventilator dependent beyond 1 week after birth, their respiratory system resistances were not found, on average, to be very high; the median respiratory system resistance was 86.5 (range 85–174) cm H 2 O/L/s.…”
Section: Methodsmentioning
confidence: 99%
“…Full unloading was the level of unloading which increased the infant's compliance to the expected 'normal', that is, 2.0 mL/ cm H 2 O/kg. If after 10 min the infant remained stable and no airway pressure waveform abnormalities were observed [4], the unloading was increased to 100 %. If airway pressure waveform abnormalities were then noted by looking at the pressure display, the unloading was to be reduced back to 75 %.…”
Section: Methodsmentioning
confidence: 99%
“…If airway pressure waveform abnormalities were then noted by looking at the pressure display, the unloading was to be reduced back to 75 %. Resistive unloading was not used as, an in vitro model, oscillations in the airway pressure waveforms appeared when the resistive unloading was greater than 100 cm H 2 O/L/s [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation